Zara cafe / Mohamad Hassan Mohd Zain, Mohamad Mustaqim Mohamad Zaki and Shah Rezzan Ag Zainal - Mohd Zain, Mohamad Hassan; Mohamad Zaki, Mohamad Mustaqim; Ag Zainal, Shah Rezzan (2018)
The company operates at Anjung Selera Alam Bina, Universiti Teknologi MARA (UiTM) Puncak Alam. The stall name is Zara Cafe. The company is one years old, which starts operating in 2017. The products and services offered are fried rice, Nasi Ayam, Nasi Kukus, Shell Out, Mee, and Bihun The business target group is focused on UiTM Puncak Alam students themselves. Zara Cafe runs business from Sunday to Friday and at 8am to 10pm. The number of staff used in this company is 4 people.